Factors influencing students’ intention to purchase counterfeit sport products / Mohamad Syafiq Mohd Sharif - Mohd Sharif, Mohamad Syafiq (Faculty of Business and Management, 2019)
The consumption of counterfeit product has attracted great attention. Therefore, this study conducted to determine the factors influencing intention to purchase counterfeit sport product. Three out of four independent variables were taken from Theory of Planned Behavior (TPB). The influencing factors consist of four elements which are attitude toward counterfeit, subjective norms, perceived behavioural control and brand consciousness. Meanwhile, the dependent variable applied in this study is students’ intention to purchase counterfeit sport product. Descriptive are causal research on the issue was applied by the researcher. Next, the sampling design for this study was non-probability sampling which is convenience sampling method with questionnaires distributed through Google form online platform. The data collected were analysed by using Statistical Package for Social Science (SPSS) version 25. The analysis includes the descriptive analysis, reliability testing, correlation and multiple regression analysis. The result of multiple regression analysis proved that three of the independent variables which are attitude toward counterfeit, perceived behavioural control and brand consciousness are significant, while subjective norms has negative significant impact on purchase intention. Therefore, future researcher suggested to conduct study using larger sample size, applying longitudinal study and broaden the focus of study.